Terapia ocupacional no campo da saúde mental infantojuvenil: revelando as ações junto aos Centros de Atenção Psicossocial Infanto-juvenil (CAPSi) - Bueno, Andressa Reiko (Universidade Federal de São Carlos, 2013)
The inclusion of children and adolescents in the mental health field was late and there s a gap between demand and offer of assistance in the field. Currently, there are actions to implement a policy on mental health of children and adolescents seeking to build a network of services, which main actions are the implementation of Psychosocial Care Centers for Children and Youth (CAPSi) and building strategies for intersectorial articulation between health mental and sectors that assist children and adolescents. The occupational therapist (OT) is a professional who makes up the team of CAPSi and is present in the process of effective actions aimed at this population. There are still few national and international studies published over the actions of the OT in child and adolescent mental health. This study aimed to characterize the inclusion of OT in CAPSi and identify the actions taken by them with users. Furthermore, it aimed to characterize the specific dynamics of CAPSi; characterize the users cared by occupational therapists in CAPSi; identify, by the perspective of occupational therapists, if CAPSi respond to Brazilian public policies of child and adolescent mental health; and identify possible gaps during graduation for OT work in the field of child and adolescent mental health. This is a descriptive study, with quantitative and qualitative approach. A total of 24 occupational therapists inserted in 18 units CAPSi the State of São Paulo participated on this study. To data collection, it was used a questionnaire, with presentation of open and closed questions. It was found that 26 of 38 units CAPSi in the State of São Paulo have occupational therapist in your staff. It was found that groups and workshops are the main programs, projects and activities offered to users and groups are the main actions to relatives. The participants assess that, even with limitations, the actions taken in the units respond to the proposals of Brazilian public policies and SUS. The only actions, which characterize the specificity of occupational therapy, undertaken by occupational therapists are related to the tools used by this professional such as analysis of activity, social inclusion and activities in daily life, as the focus on activities of daily living. It was found that the actions of occupational therapists are guided by aspects related to users such as their needs and diagnosis. Regarding gaps during graduation, the participants pointed out the insufficient content of basic/clinical disciplines on child and adolescent mental health. It s Indicated the need to reflect on the CAPSi not being the only equipment responsible for assisting the child and youth with psychological distress, necessitating the realization and consolidation of intersectoral actions to achieve psychosocial rehabilitation. It is believed that this study will assist the knowledge produced in the field of child and adolescent mental health, knowledge about the practices and training of occupational therapists in this field, as well as contribute to reflections about public policy and improving interventions.
Occupational therapy in the field of child and adolescent mental health: revealing the actions with Child and Adolescent Psychosocial Care Centers (CAPSi)
Keywords: Terapia ocupacional; Serviços de saúde mental; Adolescente; Prática profissional; Crianças; Mental health services; Child; Adolescent; Occupational therapy; Professional practice; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL